Cancer patients with potential eligibility for vascular endothelial growth factor antagonists use have an increased risk for cardiovascular diseases comorbidities. Issue 3 (March 2020) - Liu, Fei; Hidru, Tesfaldet H.; Gao, Ruiyuan; Lin, Yajuan; Liu, Ying; Fang, Fengqi; Liu, Jiwei; Li, Huihua; Yang, Xiaolei; Xia, Yunlong
Abstract : Background: Recent studies have reported the prevalence of cardiovascular diseases (CVDs) among cancer patients following the use of the vascular endothelial growth factor (VEGF) signaling inhibitors. However, data for patients with a history of cancer before active cancer treatment are lacking. This study aims to investigate the distribution of CVD-related comorbidities before cancer treatment in potential VEGF antagonists candidates. Methods: A total of 22 500 newly diagnosed cancer patients registered from 1 January 2011 to 31 December 2017 were included. Cancer patients with colorectal cancer (CRC), renal cell carcinoma (RCC), thyroid cancer, hepatocellular carcinoma (HCC), and lung cancer were selected. Results: Hypertension (HTN), coronary heart diseases, atrial fibrillation, and heart failure were top CVD comorbidities among studied cancers. HTN was the most prevalent CVD (26.0%). The prevalence of HTN in RCC, CRC (33.5 and 29.4% respectively) was significantly higher than that in HCC, lung cancer, and thyroid cancer patients (25.1, 24.5, and 23.1%, respectively). Among cancer patients with HTN, the majority of cancer patients fall in grade III (75.7%) and very high cardiovascular risk level (85.4%). Out of the 5847 HTN patients, 26% were not in antihypertensive use, and 34.2% failed to achieve the target blood pressure. Conclusion: Cancer patients carry a high burden of CVD-related comorbidities before the application of VEGF antagonists. HTN is the most prevalent comorbid condition, and cancer patients with HTN constitute substantial cardiovascular risks and a higher co-prevalence of other CVDs.